The effects of training on own and co-worker productivity: Evidence from a field experiment - Andries de Grip; Jan Sauermann (Institute for the Study of Labor (IZA), 2011)
This paper analyses the effects of work-related training on worker productivity. To identify the causal effects from training, we combine a field experiment that randomly assigns workers to treatment and control groups with panel data on individual worker performance before and after training. We find that participation in the training programme leads to a 10 percent increase in performance. Moreover, we provide experimental evidence for externalities from treated workers on their untreated teammates: An increase of 10 percentage points in the share of treated peers leads to a performance increase of 0.51 percent. We provide evidence that the estimated effects are causal and not the result of employee selection into and out of training. Furthermore, we find that the performance increase is not due to lower quality provided by the worker.
urn:nbn:de:101:1-201110102328
Keywords: J24; M53; C93; 330; training; field experiment; peer effects; productivity; Weiterbildung; Arbeitsproduktivität; Arbeitsgruppe; Test